STUDI PENGARUH PERUBAHAN TEGANGAN DAN ARUS TERHADAP SUHU PADA ALAT INKUBATOR BAYI - Aripin Triyanto; Vandanu Adiputra (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Technological advances in the world are very important, one of which is a device to help baby safety. Because the infant mortality rate is quite high. Incubator is one solution to reduce infant mortality because the baby is not born normally. Several steps were taken to standardize the voltage, current and temperature in the incubator room. With the standards that have been set, it is hoped that it will make it easier in an emergency when the incubator is ready to use. In addition, the research development was carried out with several data collection times which were influenced by room temperature. Data obtained at certain hours with temperatures according to the use of Arduino measuring instruments and assisted by simling from the web. The following data are obtained when measuring voltage, current and temperature. With an input voltage of 100 V, we get 1.7 A and a temperature of 18.2˚C. Meanwhile, using a voltage of 225 V, obtained a current of 2.7 A and a temperature of 27.5˚C. So that the results of the voltage, current and temperature data are adjusted to the standard setting on the incubator of 220 V to 230 V with a standard temperature of 37.5 to 38.5˚C.